The Effect of Curcumin on Penile Fibrotic Plaque in Rats with Experimental Peyronie’s Disease - Ulubay, Mahmut; Kaya, Ayşenur; Kaplan, Süleyman; Kaplan, Arife Ahsen; Tüfekçi, Kıymet Kübra; Akdeniz, Ekrem (LookUs Bilisim A.S., 2023)
Objective: No effective medical approach for the treatment of Peyronie’s disease (PD) has to date been described. This study was intended to evaluate the antifibrotic, antioxidant, and anti-inflammatory effects of curcumin on fibrotic tissue in the tunica albuginea (TA) in a rat model of PD. Materials and Methods: Twenty-four male Sprague Dawley rats aged 10 months were randomized into three groups (n = 8 in each). No PD model was induced in the control group. The PD+saline (PD+Ps) group received fibrin injection, followed two weeks later by saline administration by oral gavage for 14 days. The PD+Curcumin (PD+Cur) group received fibrin injection into the TA followed two weeks later by curcumin administration by oral gavage for 14 days. At the end of the experiment, fibrotic activity was evaluated using stereological and histopathological methods. Transforming growth factor-?1 (TGF-?1), one of the most fibrogenic cytokines, was evaluated using immunohistochemistry with an anti-TGF-?1 rabbit monoclonal antibody. Results: Stereological analysis revealed significantly greater Peyronie-like plaque areas in the TA in the PD+Ps group than in the control and PD+Cur groups (p<0.0001). No significant difference was observed between the control and PD+Cur groups (p=0.35). The PD+Ps group exhibited strong TGF?1 immunoreactivity with increased expression in the collagenous connective tissues and fibroblasts around the TA. Conclusion: Curcumin reduced fibrotic tissue in the TA and may represent a novel therapeutic option in the treatment of PD.
Keywords: 3. Good health